1308 VIRTUAL FRAILTY WARD - POST DISCHARGE FRAILTY SUPPORT. (16th January 2023) - Teo, A; Wright, H
Abstract: Background: In response to the COVID pandemic when new robust discharge criteria were introduced to facilitate early discharge to optimise hospital capacity, Virtual Frailty Ward (VFW) was established. VFW provides nurse-led telephone follow-up for patients discharged primarily from the Emergency Department (ED) and the Acute Frailty unit (AFU). Objectives: We aim to provide continuity of care by following up frail elderly patients at home, reviewing their medical, functional and social progress post discharge and ensuring they received adequate support to avoid hospital re-admission. Methods: The service is overseen by the Lead Frailty Practitioner, supported by Consultant Geriatricians. Calls are made Monday to Friday by a team of Advanced Specialist Nurses. The case load is split up into 3 categories with different levels of priorities – 1: at least weekly calls; 2: Fortnightly calls; 3: Monthly calls. This service engages closely with community partners such as community frailty service, social care, district nurses and general practitioners. Results: In year 1 (1/4/2020-31/3/2021), we had 598 patients on this VFW. 93 patients were referred to therapy team for urgent equipment to maintain safety, 73 patients were referred to community frailty and 112 patients had urgent discussions with GP to avoid hospital admissions. The 30 days readmissions rate was 14%. 547 patients were discharged. In year 2 (1/4/2021 – 31/3/2022), we had 297 patients. 49 patients were referred to therapy team, 32 patients were referred to community frailty team, and 41 patients required input from GP. The 30-day readmission rate was 11%. 224 patients were discharged. Conclusion: VFW is a cost- effective service that has helped to reduce length of stay of frail elderly patients in an acute hospital setting, maintaining patient safety and prevent hospital re-admission, co-ordinated with community services. Our service has been highlighted in the recent GIRFT report on improving clinical practice.